2010
DOI: 10.4137/ijis.s4801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical vs. Beetle-mediated Self-pollination in Gossypium Tomentosum (Malvaceae), an Endangered Shrub

Abstract: Experimental hand pollinations of the endangered, Hawaiian, endemic, Gossypium tomentosum Nutt. Ex. (Malvaceae) showed that it was self-compatible, but self-pollination resulted in reduced reproductive output. Field observations and pollen tube analyses using fluorescence microscopy showed that mechanical self-pollination in this species included a mechanism known as bending stigmas. A receptive stigma bent backwards and contacted dehiscent anthers in 7% of flowers found on 17 G. tomentosum plants. The yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The three species have shared habitat preferences (Wagner et al 1999) and insect pollinators (Krakos et al 2010, Pleasants and and are known to be interfertile (Meyer and Meyer 1961, Stephens 1964, DeJoode and Wendel 1992. In addition, all three species are capable of outcrossing; both alien cotton species are facultative selfpollinators and opportunistic outcrossers (Oosterhuis and Jernstedt 1999), and Hawaiian cotton primarily outcrosses (Krakos et al 2010). For these reasons, Daehler and Carino (2001) suggested that alien and native cotton species may hybridize and spread in the Hawaiian Islands.…”
Section: Assessment Of Persistence Of Hybrids Between Alien Pima Cottmentioning
confidence: 95%
See 1 more Smart Citation
“…The three species have shared habitat preferences (Wagner et al 1999) and insect pollinators (Krakos et al 2010, Pleasants and and are known to be interfertile (Meyer and Meyer 1961, Stephens 1964, DeJoode and Wendel 1992. In addition, all three species are capable of outcrossing; both alien cotton species are facultative selfpollinators and opportunistic outcrossers (Oosterhuis and Jernstedt 1999), and Hawaiian cotton primarily outcrosses (Krakos et al 2010). For these reasons, Daehler and Carino (2001) suggested that alien and native cotton species may hybridize and spread in the Hawaiian Islands.…”
Section: Assessment Of Persistence Of Hybrids Between Alien Pima Cottmentioning
confidence: 95%
“…comm.). With sufficient rainfall, Gossypium tomentosum produces flowers throughout the year (Stephens 1964), which are viable for a single day (Krakos et al 2010). Though selfcompatible, pollen tube formation is more vigorous when cross-pollinated, a mechanism that is facilitated by the extended style of the native cotton (Krakos et al 2010).…”
Section: Assessment Of Persistence Of Hybrids Between Alien Pima Cottmentioning
confidence: 99%